Health of children born to childhood cancer survivors: Participant characteristics and methods of the Multicenter Offspring Study - Sommerhäuser, Greta; Borgmann-Staudt, Anja; Schilling, Ralph; Frey, Eva; Hak, Jiri; Janhubová, Veronika; Kepakova, Katerina; Kepak, Tomas; Klco-Brosius, Stephanie; Krawczuk-Rybak, Maryna; Kruseova, Jarmila; Lackner, Herwig; et al. (Cancer epidemiology, 2021)
INTRODUCTION: Research on childhood cancer survivor offspring has been limited to genetic disease occurrence, malformations or non-hereditary cancers. However, previous surveys indicated that survivors harbor fears about their (prospective) children's overall health. Our Multicenter Offspring Study examined extensive health aspects in children born to survivors and their siblings providing comprehensive information to be used in patient counseling to elucidate and alleviate existing concerns. METHODS: Using a specifically designed questionnaire, childhood cancer survivors and their siblings were surveyed on their offspring's health (Supplementary material). Recruitment strategies depended on local infrastructures and standards of participating centers, including registry-based and direct approaches. Group differences were tested non-parametrically and effect sizes were calculated. RESULTS: In total, 1126 survivors reported on 1780 offspring and 271 siblings reported on 441 offspring. Response rates ranged from 32.1% (Czech Republic) to 85.0% (Austria). Respondents were more likely to be female (p = .007), older at time of survey (p < .001), diagnosed 1980-1999 (p < .001) and treated with chemotherapy (p < .001). Compared to siblings, survivors were younger at time of survey (35 years vs. 39 years, p < .001) and at first birth (29 years vs. 30 years, p < .001). Survivor and sibling offspring only differed in terms of age at survey (6.3 years vs. 8.9 years, p < .001). CONCLUSION: The Multicenter Offspring Study investigates a wide variety of health aspects in offspring born to survivors and their siblings in five European countries. Our study cohorts form a solid basis for future analyses; yet, certain limitations, due to differences in approach among participating centers, must be considered when interpreting findings.
Keywords: Childhood cancer; přežívající; Male; mužské pohlaví; Offspring; sourozenci; Prospective Studies; dítě; Child; Neoplasms; ženské pohlaví; přežívající onkologičtí pacienti; Humans; prospektivní studie; Survivor; nádory; Cancer Survivors; Siblings; Health; Female; lidé; Survivors